Valoración económica de espacios contaminados por hidrocarburos en la cuenca del corrientes loreto - Perú, 2007, 2008 - Sandoval Del Aguila, Jorge Ronal (2008)
This study aimed at identifying sites polluted by hydrocarbons in the Corrientes river basin, Loreto-Peru in the period 2007-2008, in order to avoid proliferation of contaminants and then to carry out remediation works. Polluted sites were identified by categories according to the risk levels, for human population, environment and others. The lots 8 and 7 in the Corrientes river were chosen because their significance and greater consideration. The qualitative-quantitative and exploratory methods were utilized, based on two field trips, on July 2007 and on January 2008; hence, areas with the highest risk level were identified.Water bodies and contaminated soils were evaluated, the chemical and physical analysis were carried out following standardized methods proposed by EPA, and the monitoring was carried out following environmental legislation recommendations. Categories identified area: Category 1, sites with risk for the human health, where the maximum allowable limits (MAL) are higher; Category 2, sites with high or medium risk for the environment; and Category 3, interest sites, for their consideration or for their high level of pollution.Old and recent polluted zones, such as Valencia/Nueva Esperanza, Capirona and Corrientes were identified; where 15 sites were categorized according to the risk type. The analysis type, the analysis performed, the type of contamination and the ongoing contamination were identified. These data were useful for the economic valuation of each site; valuation according to the proposed bioremediation-type cleaning was as follows: Valencia/Nueva Esperanza USD 389 434,00 , Capirona USD 3 027 335,84 and Corrientes/Trompeteros USD 16984 661,00, totalizing altogether USD 20 401 430,84.